THE AVIFAUNA COMPOSITION OF EL HAOUDH ‹‹ REGION OF DJEBEL AMOUR - ALGERIA - ›› - Djeldjli Abdelhadi*; Berrabah Djamal Edine**; Lyes Belaid*; Chachou Mustapha*; Boumaaraf Houssine*; Sardou Abdelhadi*; Setti Mhammed* (Natural Resources and Sustainable Development, 2022)
A monitoring of the avifauna is carried out in the wetland of El Haoudh "34° 04' N; 2° 02’ E”, North-East of the Jebel Amour region - ALGERIA - during the period 2018 - 2020. This study reveals the presence of 28 species, structured in 17 families. The total richness varies between a maximum of 25 species in 2018 and 2019 and a minimum of 24 species in 2020. The most represented families are the family of Strigidae and the family of Columbidae with 4 species each, followed by the family of Anatidae with 3 species. It should be noted that the Shannon-Weaver diversity index (H') used for the exploitation of the species counted in the study region is equal to 2.62 bits in 2018 and 1.56 bits in 2019 and 1.56 bits in 2020. The value of the even distribution is equal to 0.56, in 2018, which implies that the numbers of the species, present tend to be in balance between them, while the values of the even distribution in 2019 and 2020 are equal to 0.33 and 0.46 respectively, which implies that the numbers of the species present tend to be unbalanced between them. This study proved that the El Haoudh area is an ecologically important area. it is home to a large number of sedentary birds, as it plays a role as a crossing and breeding station during the winter period for migratory birds.